Assessing spider fear: Validity of a novel computerized behavioral avoidance test - Alexander Karner; Cindy Sumaly Lor; Mengfan Zhang; Frank Scharnowski (PLoS ONE, 2026)
Spider phobia is one of the most common specific phobias and can be highly detrimental to one’s quality of life. To evaluate the efficacy of treatments, reliable pre- and post-treatment assessments are needed. Behavioral avoidance tests (BATs), where one is asked to approach a spider, are commonly used as such measures. With the increasing popularity of computerized interventions, there is a demand for quick assessments for fear of spiders, that can be completed using computers or smartphones. Here, we tested the validity of a novel computerized BAT (cBAT) that we introduced in our previous work. In this cBAT, participants unblurred three images of spiders up to a point where they still felt comfortable viewing them. We expected that the cBAT would be moderately to strongly correlated with established measures for fear of spiders. Our analysis revealed that the cBAT showed moderate convergent and concurrent validity through correlations with self-report questionnaires indicating spider fear, and with a real-life BAT, respectively. However, the latter was no longer observed in a follow-up. While the cBAT facilitates ease of application and has a quick, straightforward participant task, we conclude that the cBAT is a limited measure for fear of spiders and might not fully capture the complexity of spider-related avoidance behavior compared to tasks that simulate real-life scenarios more closely. We propose the development of a refined cBAT that maintains an easily applicable participant task.